The Relationship Of Difficult Learning With The Results Science Study Of Students Class VIII MTsN 9 Agam Lubuk Basung Lesson Year 2018/2019 - Haany Irwan; Armen Armen; Ganda Hijrah Selaras; Ristiono Ristiono (Universitas Negeri Padang, 2019)
The low of learning values of students are caused by two main factors, there are internal and external factors. Difficult learning affect the learning values of the student which one of the kinds of internal and external factors. The aim of this study is to determine the difficult learning level, learning values, and to combine difficult learning with learning values of students class VIII science learning at MTsN 9 Agam Lubuk Basung. This research is descriptive qualitative and quantitative research. The sample of study is class VIII students at MTsN 9 Agam Lubuk Basung Academic Year 2018/2019. Data analyzed using percentage and correlation formulas, then t-test is used to find out the correlation which significant or not significant. The results show that the level of difficult learning of class VIII students MTsN 9 Agam is very high with a value 87,50%. For the level of learning values class VIII students of MTsN 9 Agam still less with a value 56,89%. Based on the results, the analysis using the correlation product moment, there is a relationship between difficult learning and learning values in students class VIII MTsN 9 Agam, and the criteria correlation still low (0.23). The result of t-test = 2,96 is formulated with t-table, each for t 5% is 0,159 and for 1% is 0,210. If looked from the t-table price, t-test is 2,96 more bigger than t-table.